PEMIDANAAN TERHADAP ANAK PELAKU TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN DIKAITKAN DENGAN ASAS KEPENTINGAN TERBAIK BAGI ANAK - Dewi Putri Nurwidiyana; Yosephine Yulita Dosniroha (The Juris, 2024)
Providing insights and perspectives on the legal field, especially the trial of criminal cases involving minors in conflict with the law. The basis of normative legal research methodology, using a case-based approach to dissect legal issues in court decisions. The core of the investigation is contained in Article 70 of Law Number 11 of 2012 concerning the Juvenile Justice System, which safeguards the rights and welfare of children caught up in criminal justice. The critical analysis of how judges interpret and apply these legal provisions aims to explain the legal mechanisms for upholding the best interests of children in criminal proceedings, investigate the complex dynamics of ensuring that children in conflict with the law receive formal legal capacity, emphasise the importance of safeguarding rights and ensuring welfare during the legal process, and contribute insights that inform and enrich the discourse around the intersection between juvenile justice, criminal law, and the principle of the best interests of the child.